Crises in the modern financial ecosystem - Giovanni di Iasio; Zoltan Pozsar (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
We build a moral hazard model to study incentives of financial intermediaries (shortly, bankers) facing a leverage-insurance trade-off in their investment choice. We demonstrate that the choice is affected by two recent transformations of the financial ecosystem bankers inhabit: (i) the rise of institutional savers, such as treasurers of global corporations, which manage huge balances in need for parking space and (ii) the proliferation of balance sheets with asset-liability mismatch, like those of insurance companies and pension funds (ICPFs), which allocate capital to bankers to reach for yield and meet their liabilities offering guaranteed returns. Bankers supply parking space to institutional savers and deliver leverageenhanced returns to ICPFs. When the demand for parking space and the mismatch which ICPFs must bridge are large, the equilibrium allocation is characterized by high leverage and financial crises. We show that post-crisis regulatory reforms, while improving the resiliency of the regulated banking sector, create room for bank disintermediation and do not unambiguously limit systemic risks which can build up in the asset management complex. Both transformations indeed stem from real economy developments (e.g. population ageing, global imbalances, income and wealth inequality, increased sophistication of tax arbitrage). Fiscal and structural reforms that directly address the real economy roots of those secular developments are then essential to complement financial and banking regulations and promote financial stability and balanced growth.
Keywords: G01; G23; G28; 330; Shadow banking; Institutional savers; Insurance companies and pension funds; Financial crisis; Leverage; Liquidity; Reach for yield